Documentação linguística das zonas raianas de Portugal e Espanha: o projeto Frontespo, com análise do caso da Beira Baixa / Extremadura espanhola - Brissos, Fernando (Revista da Associação Portuguesa de Linguística, 2017)
This paper takes on two main objectives. The first is to present and depict the project Frontespo – Frontera hispano-portuguesa: documentación lingüística y bibliográfica [Spanish-Portuguese frontier: linguistic and bibliographic documentation], which aims at producing a comprehensive linguistic documentation of the frontier area between Portugal and Spain. The second objective is to study the stressed vowel systems of a specific border area located in the central interior part of Portugal, which, despite not having been subject to a detailed depiction up to this day, is decisive in understanding the constitution of Portuguese central-southern dialects as a whole, as recent studies have shown. The results are clear in (i) allowing for the description of the area’s vowel systems and (ii) improving our view on the history of central-southern Portuguese. This study therefore exemplifies the type of linguistic approach that a project like Frontespo allows for and, more importantly, the need for new, comprehensive language documentation projects in Portugal.